Double Mutation at the Putative Protein Kinase C Phosphorylation Sites Thr151 Plus Thr323 in the Mouse LeukotrieneD4 Receptor Eliminates Homologous Desensitization - Sune T. Jørgensen; Heidi N. Eriksen; Janni Dausell; Thomas Jespersen; Ian H. Lambert; Else K. Hoffmann (Cellular Physiology and Biochemistry, 2013)
Background/Aims: Signalling via CysLT1 is involved in activation of volume sensitive K+ channels and homologous desensitization of the LTD4 receptor impairs regulatory volume decrease (RVD). The aim is to illustrate the effect of mutation of putative PKC consensus phosphorylation sites in the CysLT1R on desensitization and RVD. Methods: mCysLT1 contains 4 putative PKC consensus phosphorylation sites, and four mutants were created: Thr151Gly, Thr323Gly, Thr151Gly plus Thr323Gly, and Thr236Gly plus Ser243Gly. Functional mCysLT1 receptor activity after injection of in vitro transcribed cRNA into Xenopus laevis oocytes was visualized as a LTD4-evoked, Ca2+-activated Cl- currents recorded by two-electrode voltage clamp. Results: Repetitive LTD4 administration (100 nM) desensitized the LTD4-evoked currents in oocytes expressing wild type CysLT1. Single mutations as well as the double mutation Thr236Gly plus Ser243Gly had no or a slight effect on the LTD4 induced desensitization. However, double mutation Thr323Gly plus Thr151Gly prevented the desensitization. As a functional consequence we find that inhibition of PKC accelerates RVD and prevents the inhibitory effect of LTD4-pretreatment on RVD in Ehrlich ascites tumour cells. Conclusion: These data indicate that simultaneous PKC-mediated phosphorylation at the 2nd inner loop (Thr151) and at the C-terminal domain (Thr323) leads to mCysLT1 receptor desensitization and abrogates the RVD response following osmotic cell swelling.